Impact of healthcare inequities on survival in Mexican patients with metastatic renal cell carcinoma - Bourlon, Maria T.; Remolina-Bonilla, Yuly A.; Acosta-Medina, Aldo A.; Saldivar-Oviedo, Bruno I.; Perez-Silva, Antonio; Martinez-Ibarra, Nayeli; Castro-Alonso, Francisco Javier; Martín-Aguilar, Ana E.; Rivera-Rivera, Samuel; Mota-Rivero, Fernando; Pérez-Pérez, Perla; Díaz-Alvarado, María G.; et al. (Frontiers in Oncology, 2023)
Introduction: The survival of patients with metastatic renal cell carcinoma (mRCC) has improved dramatically due to novel systemic treatments. However, mRCC mortality continues to rise in Latin America. Methods: A retrospective, multicenter study of patients diagnosed with mRCC between 2010-2018 in Mexico City was conducted. The aim of the study was to evaluate the impact of healthcare insurance on access to treatment and survival in patients with mRCC. Results: Among 924 patients, 55.4%, 42.6%, and 1.9% had no insurance (NI), social security, (SS) and private insurance (PI), respectively. De novo metastatic disease was more common in NI patients (70.9%) compared to SS (47.2%) and PI (55.6%) patients (p<0.001). According to IMDC Prognostic Index, 20.2% were classified as favorable, 49% as intermediate, and 30.8% as poor-risk disease. Access to systemic treatment differed by healthcare insurance: 36.1%, 99.5%, and 100% for the NI, SS, and PI patients, respectively (p<0.001). NI patients received fewer lines of treatment, with 24.8% receiving only one line of treatment (p<0.001). Median overall survival (OS) was 13.9 months for NI, 98.9 months for SS, and 147.6 months for NI patients (p<0.001). In multivariate analysis, NI status, brain metastases, sarcomatoid features, bone metastases, no treatment were significantly associated with worse OS. Conclusion: OS in mRCC was affected by insurance availability in this resource-limited cohort of Mexican patients. These results underscore the need for effective strategies to achieve equitable healthcare access in an era of effective, yet costly systemic treatments.